2016
DOI: 10.1016/j.yjmcc.2016.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Na + -Ca 2+ exchange in the heart: Allosteric activation, spatial localization, sparks and excitation-contraction coupling

Abstract: The cardiac sodium (Na+)/calcium (Ca2+) exchanger (NCX1) is an electrogenic membrane transporter that regulates Ca2+ homeostasis in cardiomyocytes, serving mainly to extrude Ca2+ during diastole. The direction of Ca2+ transport reverses at membrane potentials near that of the action potential plateau, generating an influx of Ca2+ into the cell. Therefore, there has been great interest in the possible roles of NCX1 in cardiac Ca2+-induced Ca2+ release (CICR). Interest has been reinvigorated by a recent super-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 83 publications
3
26
0
Order By: Relevance
“…In NCX3, alternative splicing involves only three exons (A, B, and C), whereas both mutually exclusive exons, A and B, are expressed in neurones and glia (Giladi et al , 2015; Chu et al , 2016; Lee et al , 2016; Tal et al , 2016; Giladi et al , 2017). In A-exon-containing NCX1 variants, CBD2 binds two Ca 2+ ions, whereas in B-exon-containing NCX1 variants, CBD2 does not bind Ca 2+ (Giladi et al , 2012).…”
Section: Sodium-calcium Exchanger: the Key Element Of Na+/ca2+ Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…In NCX3, alternative splicing involves only three exons (A, B, and C), whereas both mutually exclusive exons, A and B, are expressed in neurones and glia (Giladi et al , 2015; Chu et al , 2016; Lee et al , 2016; Tal et al , 2016; Giladi et al , 2017). In A-exon-containing NCX1 variants, CBD2 binds two Ca 2+ ions, whereas in B-exon-containing NCX1 variants, CBD2 does not bind Ca 2+ (Giladi et al , 2012).…”
Section: Sodium-calcium Exchanger: the Key Element Of Na+/ca2+ Signalmentioning
confidence: 99%
“…Computer-aided modelling reveals NCX can significantly contribute to Ca 2+ -induced Ca 2+ -release (CICR) in cardiomyocytes (Chu et al , 2016), when taking into account experimentally obtained parameters of allosteric regulation of cardiac NCX and high-resolution cell-imaging of subcellular NCX location in cardiomyocyte (Chu et al , 2016). According to this model, increasing the fraction of NCX in the dyad and peri-dyadic (PD) domains decreases frequency and fidelity of Ca 2+ sparks, as well as diastolic [Ca 2+ ] i , although amplitude and duration of Ca 2+ sparks are less sensitive to NCX spatial redistribution.…”
Section: Sodium-calcium Exchanger: the Key Element Of Na+/ca2+ Signalmentioning
confidence: 99%
“…Additionally, we assumed that each CRU in the network has the same number of LTCC and RyRs, thereby neglecting heterogeneities in CRU properties that may be present (40,51) and could potentially affect the distributions of local Ca 2þ spark amplitudes and local NCX currents. Moreover, we have only considered one specific NCX model, and whether similar effects occur with other available NCX models remains to be investigated (52). Finally, we have neglected the spatial variation of Ca 2þ within the submicron dyadic space.…”
Section: Limitationsmentioning
confidence: 99%
“…However, the concrete mechanisms of Ca 2+ transients are diverse and uncertain. Several studies have shown that the increase of [Ca 2+ ] i is induced by the influx of extracellular Ca 2+ via membrane Ca 2+ channels or Na + /Ca 2+ exchangers34. However, the increase of intracellular Ca 2+ also can be resulted from the mobilization of sarcoplasmic reticulum (SR) during acidosis56.…”
mentioning
confidence: 99%